30. ATTITUDES ON HIV/AIDS INJECTION AMONG NURSING STUDENTS IN HAI DUONG MEDICAL TECHNICAL UNIVERSITY (Vietnam Journal of Community Medicine, 2025)
Objective: To describe attitudes on HIV/AIDS infection among nursing students at Hai Duong Medical Technical University in 2020; to identify the association between attitudes on HIV/AIDS infection and the length of study of nursing students.Method: A cross-sectional descriptive study at Hai Duong Medical Technical University for nursing students in 2020.Results: The proportion of students attained positive attitudes towards HIV/AIDS was 13.7%. Only 40.4% of students identified the current increasing risk of unsafe homosexual sex, especially among homosexual men. People believe they have the right to refuse care for HIV patients is 63.7%. Students feel anxious when caring for HIV patients, accounting for 92.6%. Students will feel reluctant to care for HIV patients is 80.4%. 77.8% agreed that they would inform family members of HIV patients about their disease status even if the patient did not agree. And the number of people who will warn other staff that a patient has HIV even if the patient does not agree is 81.9%. Female students have a general attitude about HIV/AIDS transmission that is 1.2 times more positive than male students, the difference was statistically significant.Conclusion: The majority of students participating in the study had negative attitudes towards HIV-related issues, accounting for 86.3%. The percentage of students with positive attitudes was 13.7%. Female students had a general attitude towards HIV/AIDS transmission that was 1.2 times more positive than male students, a statistically significant difference. Nursing students need to have a professional attitude at work, especially when working in sensitive and difficult positions.
Keywords: Attitude; HIV/AIDS; nursing students.